Integrative Learning Approaches in Fostering Gender Equality Competence - Alejo, Evita Marie G.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2025)
The study's primary objective is to investigate how the integrative learning approach contributes to fostering gender equality competence. Schools are a pivotal environment for the youth, thus, they are expected to be safe, non-discriminatory, and provide equal treatment and education. This study aims to understand how integrative learning approaches increase gender equality competence. Descriptive and Correlational Research was utilized as these research aims to determine the relationship of gender equality competence to integrative learning approaches and if gender significantly affects the relationship between the two variables mentioned above. The research instrument used in this study is a self-made survey checklist that was completed based on various scholars and literature. In this study, the researcher employed the stratified sampling technique using a convenience sampling procedure where availability and willingness were factors for selecting the respondents. The researchers utilized convenience sampling to gather research data from several respondents who were conveniently accessible within the researcher’s proximity. The outcome of testing for a significant relationship between integrative learning approaches and gender equality competence revealed no moderation effect among the variables. With the result, findings can be utilized in further improving the curricula and emphasizing the utilization of necessary procedures on basing learning methods on gender-related approaches.